A Modified Ascending Aortic Cannulation Technique in Minimally Invasive Totally Thoracoscopic Cardiac Surgery - Liao,Shengjie (2022)
ABSTRACT Cannulation through the femoral artery is the preferred method of establishing peripheral cardiopulmonary bypass in minimally invasive totally thoracoscopic cardiac surgery. However, faced with the contraindication of femoral artery cannulation, modified ascending aortic cannulation is an alternative approach to minimally invasive totally thoracoscopic cardiac surgery.